Autosomal-recessive complicated spastic paraplegia with a novel lysosomal trafficking regulator gene mutation. Issue 9 (12th February 2014) - Shimazaki, Haruo; Honda, Junko; Naoi, Tametou; Namekawa, Michito; Nakano, Imaharu; Yazaki, Masahide; Nakamura, Katsuya; Yoshida, Kunihiro; Ikeda, Shu-ichi; Ishiura, Hiroyuki; Fukuda, Yoko; Takahashi, Yuji; et al.
Abstract : Background: Autosomal-recessive hereditary spastic paraplegias (AR-HSP) consist of a genetically diverse group of neurodegenerative diseases characterised by pyramidal tracts dysfunction. The causative genes for many types of AR-HSP remain elusive. We tried to identify the gene mutation for AR-HSP with cerebellar ataxia and neuropathy. Methods: This study included two patients in a Japanese family with their parents who are first cousins. Neurological examination and gene analysis were conducted in the two patients and two normal family members. We undertook genome-wide linkage analysis employing single nucleotide polymorphism arrays using the two patients' DNAs and exome sequencing using one patient's sample. Results: We detected a homozygous missense mutation (c.4189T>G, p.F1397V) in the lysosomal trafficking regulator ( LYST ) gene, which is described as the causative gene for Chédiak–Higashi syndrome (CHS). CHS is a rare autosomal-recessive syndrome characterised by hypopigmentation, severe immune deficiency, a bleeding tendency and progressive neurological dysfunction. This mutation was co-segregated with the disease in the family and was located at well-conserved amino acid. This LYST mutation was not found in 200 Japanese control DNAs. Microscopic observation of peripheral blood in the two patients disclosed large peroxidase-positive granules in both patients' granulocytes, although they had no symptoms of immune deficiency or bleeding tendency. Conclusions: We diagnosed these patients as having adult CHS presenting spastic paraplegia with cerebellar ataxia and neuropathy. The clinical spectrum of CHS is broader than previously recognised. Adult CHS must be considered in the differential diagnosis of AR-HSP.